2018
DOI: 10.1097/mcp.0000000000000508
|View full text |Cite
|
Sign up to set email alerts
|

New treatment paradigms for connective tissue disease-associated interstitial lung disease

Abstract: Ultimately, further research into the mechanisms linking autoimmunity to fibrosis and randomized controlled clinical trials are needed, with the aim of preventing irreversible damage of lung tissue, while minimizing burden of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…These therapies have been shown to improve parameters of pulmonary function that are related to prognosis, such as DLCO, DLCO/ FVC and TLC [45,50,51], but to date no study has actually demonstrated improved survival in patients treated with immunosuppressive agents. Hence, there is a need for new parameters that better predict long time survival under immunosuppression [52].…”
Section: Discussionmentioning
confidence: 99%
“…These therapies have been shown to improve parameters of pulmonary function that are related to prognosis, such as DLCO, DLCO/ FVC and TLC [45,50,51], but to date no study has actually demonstrated improved survival in patients treated with immunosuppressive agents. Hence, there is a need for new parameters that better predict long time survival under immunosuppression [52].…”
Section: Discussionmentioning
confidence: 99%
“…Once the diagnosis of SSc-ILD is established, it is important for the treating clinician to identify the constellation of factors that designate one patient to receive routine monitoring (as their risk for progressive ILD may be low), and for another patient to initiate or escalate immunomodulatory treatment (as risk for progressive ILD is high; Table 1) 18,19 .…”
Section: Screening and Monitoringmentioning
confidence: 99%
“…Interstitial lung disease (ILD) includes a heterogeneous group of parenchymal lung pathologies with different clinical, histological, radiological, and serological features (1). To correctly classify ILD is crucial, since follow-up, treatment, and prognosis are strongly dependent on ILD subtype (2,3). Considering that ILD may complicate the course of any connective tissue disease (CTD) and that signs of CTD are frequently not easy to identify (4-7), an underlying CTD should be ruled out in every ILD, even when the suspect is low or even absent.…”
Section: Introductionmentioning
confidence: 99%